Ki-67 marker useful for classification of malignant invasive ductal breast cancer - Irmawati Hassan; Twidy Tarcisia; Agnestina Agnestina; Santoso Cornain; I Made Nasar (Universa Medicina, 2013)
BACKGROUND Breast cancer is an important health problem in the world. Uncontrolled cell proliferation represents a malignant characteristic of neoplasia such as breast cancer, and can be examined immunohistochemically by measuring the Ki-67 proliferative marker. The objective of this study was to determine the role of Ki-67 for classification of the degree of malignancy in women with invasive ductal breast cancer.METHODSA cross-sectional study was conducted on 20 women with invasive ductal breast cancer. The samples were immuno-histochemically tested for Ki-67 using anti-Ki-67 primary antibody. The Ki-67 proliferative index was determined by enumerating the proportion of Ki-67 positive nuclei among the total number of cells in ten areas observed at 400x magnification, using a 20% cut-off value to distinguish between low and high proliferative indices. Statistical analysis was by means of the chi-square test.    RESULTSSeventy five persent of the high grade malignancies had a high Ki-67 proliferative index (>20%), while only 12.5% of the low grade malignancies had a high Ki-67 index (>20%). The difference in grade malignancy was statistically significant (p=0.022), whereas tumor size was not associated with a statistically significant difference in Ki-67 index (p=0.648). CONCLUSIONThe study showed that invasive ductal breast cancer with high Ki-67 index was significantly associated with high grade of malignacy. The high Ki-67 marker index can be used for classification of the grade of malignancy of invasive ductal breast cancer.